Chemical Composition of Some Non-Conventional and Local Feed Resources for Poultry in Sudan - Babiker , M.S. (International Journal of Poultry Science, 2012)
Groundnut meal is used commercially as the main protein source for poultry diets in Sudan. Because of the higher price and scarcity of groundnut meal from time to time this study has been carried out to find alternative protein resources for poultry diets. Also, to contribute to the feed supply and to solve the problem of the limited availability of poultry feedstuffs in Sudan; Crude Protein (CP), Crude Fibre (CF), fat, Nitrogen Free Extract (NFE), Metabolizable Energy (ME); mineral content and amino acids composition have been determined for some non-conventional and local feed resources. Groundnut cake, sesame cake and sunflower cake had high CP contents (53.44, 44.42 and 31.57%) respectively, whereas baobab seed cake (Adansonia digitata L) had the lowest value (15.01%) among all plant samples. The highest ash value was recorded with earthworm (Lumbricus terrestris) sample (43.5%) followed by Moleita Baladi (Sonchus oleraceus) (22.53%) and sesame cake (14.15%). Moringa oleifera seeds and leaves had the highest ME (12.39 and 11.88 MJ/kg), respectively. The greatest CF was observed with cotton seed cake (29.6%). The highest calcium percentage among all seeds cakes was recorded with sesame seed cake (1.93%). Moringa leaves had the greatest calcium value among the rest of the determined samples (2.70%). Sesame cake was the best sample for the phosphorus content (1.17%). The highest values of cooper, zinc and manganese were 109.86, 151.17 and 268.73 mg/kg, respectively. Those values were observed with earthworm. Sesame cake had the greatest value of methionine among all samples (1.29%), while baobab seed cake had the lowest one (0.19%). Earthworm and groundnut cake had the greatest lysine content 2.56 and 1.82%, respectively. Most of determined amino acids were above than 1% in all tested oil seed cakes. Although the amino acids contents in all tested samples were proportionally high, some of the samples had deficiency in particular amino acids. These results encourage the inclusion of several protein resources to avoid the amino acids deficiency when poultry diets are formulated. This study indicated that these non-conventional and local feed resources can be used in poultry diets in Sudan, but because of the presence of secondary compounds, the amount of the feedstuffs used should be decided through further research.